2021
DOI: 10.1016/j.atmosenv.2021.118715
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear response of nitrate to NOx reduction in China during the COVID-19 pandemic

Abstract: In recent years, nitrate plays an increasingly important role in haze pollution and strict emission control seems ineffective in reducing nitrate pollution in China. In this study, observations of gaseous and particulate pollutants during the COVID-19 lockdown, as well as numerical modelling were integrated to explore the underlying causes of the nonlinear response of nitrate mitigation to nitric oxides (NO x ) reduction. We found that, due to less NO x titration e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 59 publications
(56 reference statements)
1
17
0
Order By: Relevance
“…These discrepancies highly depended on the different study areas and the duration of the lockdown period. O 3 enhancement during the COVID-19 lockdown resulting from less NOx titration has been proposed previously over other regions such as cities in China ( Meng et al, 2021 ; Ren et al, 2021 ; Wu et al, 2021 ; Yin et al, 2021 ), Baghdad, Iraq ( Hashim et al, 2021 ), Milan, Italy ( Zoran et al, 2020 ) and the Auvergne-Rhône-Alpes region, France ( Sbai et al, 2021b ). During the lockdown in Europe, O 3 was found to increase over more urbanized regions such as Central Northern Europe and the Po Valley ( Cuesta et al, 2021 ; Grange et al, 2021 ; Matthias et al, 2021 ; Sbai et al, 2021b ; Zoran et al, 2020 ); O 3 photochemistry in these regions with high NOx emissions from industry and traffic was typically dominated by VOC-limited conditions and O 3 titration with NO was reduced when NOx emissions were reduced ( Cuesta et al, 2021 ; Matthias et al, 2021 ).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…These discrepancies highly depended on the different study areas and the duration of the lockdown period. O 3 enhancement during the COVID-19 lockdown resulting from less NOx titration has been proposed previously over other regions such as cities in China ( Meng et al, 2021 ; Ren et al, 2021 ; Wu et al, 2021 ; Yin et al, 2021 ), Baghdad, Iraq ( Hashim et al, 2021 ), Milan, Italy ( Zoran et al, 2020 ) and the Auvergne-Rhône-Alpes region, France ( Sbai et al, 2021b ). During the lockdown in Europe, O 3 was found to increase over more urbanized regions such as Central Northern Europe and the Po Valley ( Cuesta et al, 2021 ; Grange et al, 2021 ; Matthias et al, 2021 ; Sbai et al, 2021b ; Zoran et al, 2020 ); O 3 photochemistry in these regions with high NOx emissions from industry and traffic was typically dominated by VOC-limited conditions and O 3 titration with NO was reduced when NOx emissions were reduced ( Cuesta et al, 2021 ; Matthias et al, 2021 ).…”
Section: Resultsmentioning
confidence: 61%
“…In particular, the phenomenon of elevated ozone levels during the lockdown periods has been extensively reported ( He et al, 2021 ; Meng et al, 2021 ; Sbai et al, 2021b ; Wu et al, 2021 ; Yin et al, 2021 ). Previous studies have analyzed the reasons for O 3 changes from the perspective of emission restrictions and meteorological factors including relative humidity, temperature, solar radiation, and ozone-forming mechanisms ( Meng et al, 2021 ; Mor et al, 2021 ; Ren et al, 2021 ; Saxena and Raj, 2021 ; Tibrewal and Venkataraman, 2022 ; Tobias et al, 2020 ). An increase in air temperature and a rise in solar radiation was responsible for the O 3 increase during the lockdown because higher temperatures could decrease the stability of the atmosphere and correspondingly increase the mixing height of pollutants, and stronger solar radiation could have enhanced the intensity of photochemical reactions in the atmosphere ( Dang and Liao, 2019 ; Mor et al, 2021 ; Ravindra et al, 2019 ; Saxena and Raj, 2021 ; Sbai et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…4). During this period, the SNA contributed 55.3 % to the total PM 2.5 , slightly higher than those of the cities in northern China such as Xi'an (50.0 %; Tian et al, 2021) and Beijing (48.5 %; Ren et al, 2021) and lower than the cities in southern China such as Guangzhou (78.7 %; Wang et al, 2021), Nanjing (68.2 %; Ren et al, 2021) and Shanghai (75.4 %; Chen et al, 2020). Sulfate was the predominant component of SNA in Hohhot during this period, whereas nitrite was the main contributor to SNA in Guangzhou, Nanjing and Shanghai.…”
Section: Temporal Variation In Pmmentioning
confidence: 82%
“…An increase in the oxidation capacity (O 3 ) of the atmosphere led to the enhancement of sulfur oxidation ratio, and then SO 4 2− formation during the COVID lockdown ( Duan et al, 2021 ). Ren et al (2021) reported that a 26–61% reduction of NOx emissions only lowered surface HNO 3 by 2–3% and enhanced the NO 3 − formation in the presence of a high concentration of NH 3 reduction in China during the COVID-19 pandemic due to the enhanced atmospheric oxidizing capacity.…”
Section: Resultsmentioning
confidence: 99%